Financial Crisis, US Unconventional Monetary Policy and International Spillovers - Chen, Qianying (IMF Working Papers; Working Paper ;, 2015)
We study the impact of the US quantitative easing (QE) on both the emerging and advanced economies, estimating a global vector error-correction model (GVECM) and conducting counterfactual analyses. We focus on the effects of reductions in the US term and corporate spreads. First, US QE measures reducing the US corporate spread appear to be more important than lowering the US term spread. Second, US QE measures might have prevented episodes of prolonged recession and deflation in the advanced economies. Third, the estimated effects on the emerging economies have been diverse but often larger than those recorded in the US and other advanced economies. The heterogeneous effects from US QE measures indicate unevenly distributed benefits and costs.